Association of the independent polymorphisms in CDKN2A with susceptibility of acute lymphoblastic leukemia. Issue 3 (27th June 2018) - Zhou, Xueyan; Liao, Fei; Zhang, Junlong; Qin, Yun; Xu, Heng; Ding, Zhenyu; Zhang, Yan; Zhang, Feng
Abstract : Acute lymphoblastic leukemia (ALL) is the most common cancer in children, and alterations in CDKN2A were considered to play an important role on leukemogenesis. Two single nucleotide polymorphisms (SNPs) at CDKN2A locus were identified to impact on ALL susceptibility via genome wide association studies, and followed by multiple subsequent replication studies at the specific hits. Here, we conducted a systematic review and meta-analysis to re-evaluate the association of both SNPs (rs3731217 and rs3731249) with ALL susceptibility by gathering the data from 24 independent studies, totally containing 7922 cases/21503 controls for rs3731217 and 6295 cases/24191 controls for rs3731249. Both SNPs were significantly associated with ALL risk (odds ratio [OR] = 0.72 and 2.26 respectively), however, exhibit race-specific pattern. In summary, our meta-analysis indicated that two SNPs at CDKN2A locus are associated with ALL susceptibility independently mainly in Caucasians. Future large-scale studies are required to validate the associations in other ethnicities.